(untitled) (Research, Society and Development, 2023)
Purpose: Compare the roughness of self-curing acrylic resin and the flexural strength of nickel-chrome (Ni-Cr) wires of orthodontic appliances submitted to different cleaning processes. Materials and methods: Samples were made with NiCr orthodontic wires bent into a “T” loop and embedded in self-curing acrylic resin and submitted to four different cleaning procedures (n = 21): Group 1 – immersion for 15 minutes in deionized water and active oxygen-based tablet; Group 2 - immersion for 15 minutes in chlorhexidine 0.12%; Group 3 – spray with chlorhexidine 0.12% solution; and Group 4 – immersion in deionized water (control) por 15 minutes twice a day. Flexural strength of the orthodontic wire and roughness of the acrylic resin surface were determined at baseline as well as 90 and 120 days using an optical microscope. Normality of the data was determined using the Shapiro-Wilk test. The Kruskal-Wallis and Mann-Whitney tests were used for comparisons of surface roughness. ANOVA followed by Duncan’s post hoc test was used for the comparison of flexural strength (α = 0.05). Results: No significant difference in surface roughness was found, except in Group 4, in which the last reading (2.25 ± 0.89) was significantly higher than the baseline reading (1.15 ± 0.27) (p = 0.013). Significant reductions in the flexural strength of the wires occurred in all groups (p = 0.002). Conclusions: Immersion in the cleaning solutions did not alter the surface roughness of the acrylic resin but promoted a reduction in the flexural strength of the wires.